2016
DOI: 10.3389/fmicb.2016.01715
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Colistin Resistance-Associated Mutations on the Fitness of Acinetobacter baumannii

Abstract: Acinetobacter baumannii had emerged as an important nosocomial and opportunistic pathogen worldwide. To assess the evolution of colistin resistance in A. baumannii and its effect on bacterial fitness, we exposed five independent colonies of A. baumannii ATCC 17978 to increasing concentrations of colistin in agar (4/5) and liquid media (1/5). Stable resistant isolates were analyzed using whole genome sequencing. All strains were colistin resistant after exposure to colistin. In addition to the previously report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 28 publications
3
40
0
Order By: Relevance
“…Colistin resistance acquisition resulted in the alteration of the antibiotic resistance profiles. This may be attributed to gene mutations responsible for the displayed resistance, leading to variations in the permeability of the outer membrane [39]. This was suggested by the changes observed in the cell morphology due to alteration of LPS, as confirmed by our investigation and other studies that linked the inactivation of LpxD to colistin resistance [40]., Knowledge concerning colistin resistance mechanisms in A. baumannii isolates of clinical origin remains limited.…”
Section: Discussionsupporting
confidence: 79%
“…Colistin resistance acquisition resulted in the alteration of the antibiotic resistance profiles. This may be attributed to gene mutations responsible for the displayed resistance, leading to variations in the permeability of the outer membrane [39]. This was suggested by the changes observed in the cell morphology due to alteration of LPS, as confirmed by our investigation and other studies that linked the inactivation of LpxD to colistin resistance [40]., Knowledge concerning colistin resistance mechanisms in A. baumannii isolates of clinical origin remains limited.…”
Section: Discussionsupporting
confidence: 79%
“…102 Interestingly, in both K. pneumoniae and A. baumannii, genomic sequencing studies have found mutations in a common regulatory pathway controlling LPS modification systems, indicating that LPS modification is key to resistance in both species. [103][104][105] This genomederived hypothesis that altered LPS modification underlies resistance was ultimately confirmed for both organisms by comparing LPS modifications in susceptible and resistant isolates. 103,106 An important caveat in studying resistance evolution in individual patients is that the larger epidemiological significance of observed resistance mutations or mechanisms cannot necessarily be inferred.…”
Section: Mutational Modes Of Resistancementioning
confidence: 90%
“…The prospect of widespread colistin resistance is of great concern, as there are limited treatment options beyond colistin for the treatment of infections caused by carbapenemase‐producing Gram‐negatives, such as K. pneumoniae and A. baumannii . Interestingly, in both K. pneumoniae and A. baumannii , genomic sequencing studies have found mutations in a common regulatory pathway controlling LPS modification systems, indicating that LPS modification is key to resistance in both species . This genome‐derived hypothesis that altered LPS modification underlies resistance was ultimately confirmed for both organisms by comparing LPS modifications in susceptible and resistant isolates …”
Section: Evolution Of Antibiotic Resistancementioning
confidence: 93%
“…To date only chromosomally encoded colistin resistance mechanisms have been reported in A. baumannii. Mutations in the pmrB/pmrA/pmrC operon and genes encoding lipid A biosynthesis (lpxA, lpxC, lpxD) confer colistin resistance through modification of the lipid A component of the lipopolysaccharide (LPS) and through complete loss of LPS, respectively (Moffatt et al, 2010;Adams et al, 2009;Mu et al, 2016). The presence of the insertion sequence ISAba11 in lpxC or lpxA also causes inactivation of LPS production (Moffatt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%